Criminal Justice Education Quality Assurance and Program Standard: Implications from a Document Analysis of SUCs Evaluation Reports - Patalinghug, Mark Erana; Morrok, Abelardo Pena; Gilaga, Bernard Godito (Jurnal Pendidikan Progresif, 2023)
Criminal Justice Education Quality Assurance and Program Standard: Implications from a Case Study of SUCs Evaluation Reports. Objectives: This study described the areas of deficiencies and compliance with the program standard as the basis for the Certificate of Program Compliance (COPC) issuance for Criminal Justice Education (CJE). Methods: Document analysis was the research method utilized in this study to examine the quality assurance and program standard deficiencies and compliance of six state colleges and universities (SUCs) with CJE programs in Region 9 of the Philippines. The data used for this study were the evaluation reports submitted by the Regional Quality Assurance Team (RQAT) after each onsite inspection conducted in 2020, 2021, and 2022. Findings: Results from the evaluation reports identified commonalities in the deficiencies noted and the recommended corrective actions. Conclusion: Based  on the findings, physical facilities, laboratory holdings, and library holdings appear to be the areas that require improvement among SUCs. Keywords: program standard, quality assurance for criminal justice education, certificate of program compliance.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202326